Peran Kepemimpinan Kepala Sekolah terhadap Kinerja dan Kedisiplinan Guru - Istiningsih, Dini; Imron, I; Mawardi, Imam (Prosiding University Research Colloquium, 2023)
This study aims to determine the leadership role of school principals in improving teacher performance and discipline. Principal leadership is very influential on school development, especially for teacher performance and discipline, where the teacher's role is also needed in improving the quality of student abilities and can be seen from the teaching and learning process. This study used a qualitative approach using observation, interviews, and documentation as data collection techniques. The results of this study indicate that the Principal's Leadership Role at Ngluwar 2 Public Elementary School, Ngluwar District, Magelang Regency in improving the performance of the principal teacher always provides guidance and direction for the intended results and as a result the students of Ngluwar 2 Public Elementary School get achievements from the MAPSI, FTBI, and Story Telling.. Whereas in terms of discipline the school principal requires teachers to attend online-based application systems (SIABA). There are several supporting and inhibiting factors in the Leadership Role of the Principal of SD Negeri Ngluwar 2 Ngluwar District, Magelang Regency, namely the availability of facilities and infrastructure, and the existence constraints in human resources.